Mycobacterium sherrisii Lung Infection in a Brazilian Patient with Silicosis and a History of Pulmonary Tuberculosis - Carolina de Oliveira Abrão; João Alves de Araújo Filho (Case Reports in Infectious Diseases)
Nontuberculous mycobacteria (NTM) diseases became relevant with the emergence and spread of HIV and are also related to lung infection in non-HIV individuals with structural lung diseases. Mycobacterium sherrisii is a NTM first characterized in 2004. Only a few cases have been reported. The aim of this case report is to describe the first detailed case of infection with M. sherrisii in a patient with silicosis and history of pulmonary tuberculosis. A 50-year-old HIV-negative white male, previous smoker, with silicosis and a history of treated pulmonary tuberculosis developed a worsening of cough and expectoration pattern, and two sputum samples were positive for acid-fast bacilli. Presumptive treatment for pulmonary tuberculosis was initiated with rifampin, isoniazid, pyrazinamide, and ethambutol, but, at month 5 of treatment, despite correct medication intake and slight improvement of symptoms, sputum bacilloscopy remained positive. Sputum cultures were positive Mycobacterium sherrisii. Treatment regimen was altered to streptomycin (for 2 months), ethambutol, clarithromycin, rifabutin, and trimethoprim-sulfamethoxazole. M. sherrisii should be considered a possible etiological agent of lung infections in patients with pneumoconiosis and history of tuberculosis.